Novel delivery systems with nonsteroidal anti-inflammatory drugs - Cvijić Sandra; Parojčić Jelena (Pharmaceutical Association of Serbia, Belgrade, Serbia, 2016)
Chronic use of oral nonsteroidal anti-inflammatory drugs (NSAIDs) is associated with increased risk of serious gastrointestinal side effects. Therefore, recent trends in the development of NSAIDs aim to reduce the incidence of side effects, and improve patient compliance. One of the strategies to improve efficacy and safety of oral NSAIDs is the development of combination products that contain gastroprotective agents. Several products containing NSAID in combination with proton pump inhibitors (ketoprofen/omeprazole, naproxen/esomeprazole), H2-receptor antagonists (ibuprofen/famotidine), and prostaglandin analogues (diclofenac/misoprostol) are currently available on the market. Another approach refer to the special formulation design to allow dose reduction while preserving drug therapeutic efficacy. An example is SoluMatrix® technology, a manufacturing process that produce submicron-sized drug particles with enhanced dissolution and absorption properties. Patented SoluMatrix® technology has been successfully employed to develop low-dose diclofenac, meloxicam, indomethacin and naproxen products. Topical NSAID formulations enable drug delivery to target tissues, while reducing systemic exposure and concomitant side effects associated with oral NSAIDs. Dermal/transdermal NSAID delivery systems are subject of intensive investigation. So far, several 'advanced' drug delivery systems with diclofenac, ibuprofen and ketoprofen have been designed.